The utility of split function testing in determining recovery of glomerular filtration rate after living kidney donation: a cohort study - Kirsty J. Crowe; Siobhan K. McManus; Julie A. Glen; Karen S. Stevenson; Ian M. McLaughlin; Alice Nicol; Colin C. Geddes (BMC Nephrology)
Abstract Background A number of UK transplantation centres use isotope studies to estimate the relative contribution from each kidney in living kidney donor assessment. The evidence that the estimation of pre-donation split function of the non-donated kidney influences post-donation renal recovery is limited. The aim of this study was to analyse whether, in the context of other donor factors, the split function of the non-donated kidney predicts the percentage recovery of glomerular filtration rate (GFR) at one-year post-donation. Methodology A retrospective cohort analysis was undertaken on 291 living kidney donors in the Glasgow Renal and Transplant Unit between 1st January 2011 and 1st June 2022. Univariable and multivariable linear regression analysis was used to analyse the impact of donor factors on recovery of renal function at one year relative to baseline isotope GFR (iGFR) or to estimated GFR (eGFR by Chronic Kidney Disease Epidemiology Collaboration [CKD-EPI] formula). Sub-analyses of donor outcome (% recovery of iGFR and eGFR at one year) were undertaken using single-measures ANOVA and grouping of donors by pre-donation isotope uptake of the non-donated kidney. Results Median recovery of pre-donation GFR at 1 year was 70.0% (IQR 64.8-75.5). On linear regression analysis there was no significant association found between split function of the non-donated kidney and the percentage recovery of iGFR, although a small significant association was found for eGFR. There was no significant difference between mean iGFR or eGFR recovery on sub-analysis of donor outcomes. Conclusions This study demonstrated no clinically important predictive relationship between percentage recovery of renal function at 1 year after living kidney donation and pre-donation split function within the range accepted for donation in our centre.